Aerospace series. Bearing, spherical plain, in corrosion resisting steel with self-lubricating liner, low starting torque and low friction coefficient, elevated duty cycles under low oscillations at different operating conditions, narrow series. Dimensions and loads for narrow series Part 1, (30th October 2019) - British Standards Institution,
No abstract available